Perceptions about local ART adherence norms and personal adherence behavior among adults living with HIV in rural Uganda - Perkins, Jessica M.; Kakuhikire, Bernard; Baguma, Charles; Rasmussen, Justin D.; Satinsky, Emily N.; Kiconco, Allen; Kananura, Justus; Audet, Carolyn M.; Siedner, Mark J.; Haberer, Jessica E.; Bangsberg, David R.; Tsai, Alexander C. (AIDS and Behavior, 2022)
Although misperceived norms often drive personal health behaviors, we do not know about this phenomenon in the context of antiretroviral therapy (ART) adherence. We conducted a cross-sectional study including all persons living with HIV (PLWH) on ART across eight villages in one parish in a rural region of southwestern Uganda. We used surveys to measure personal reports of ART adherence (not missing any doses of ART in the past 7 days was considered optimal adherence whereas missing doses was considered sub-optimal adherence) and perceived norms about the local ART adherence norm (whether or not each individual thought ‘most other PLWH on ART in this parish’ missed any doses in the past 7 days). Multivariable Poisson regression models were used to estimate the association between perceived norms and personal adherence. Among 159 PLWH on ART (95% response rate), 142 (89%) reported no missed doses. However, 119 (75%) thought most individuals in this population of PLWH on ART were sub-optimally adherent. This misperception about the local ART adherence norm was prevalent in every subgroup of PLWH. Misperceiving the local ART adherence norm to be sub-optimal adherence was associated with a reduced likelihood of optimal adherence among married PLWH (adjusted relative risk [aRR] = 0.83, 95% confidence interval [CI] 0.71–0.97). The association was similar but imprecisely estimated for all PLWH (aRR = 0.91, 95% CI 0.82–1.01). Interventions to correct misperceived ART adherence norms as a stand-alone intervention or as a complement to other adherence promotion programs may influence ART adherence behavior and perhaps reduce HIV-related stigma.
Keywords: Antiretroviral therapy; Descriptive norms; Social networks; Social norms; Stigma